Wedding Traditions in Madurese Culture A Study of Values, Rituals, and Gender Roles in the Marriage Process in Mekar Sari Village, Kubu Raya Regency - Amira Fazilah; Nurul Fadilah; Mentari (Universitas Muhammadiyah Palu, 2025)
This study aims to explore wedding traditions within Madurese culture, focusing on the values, rituals, and gender roles involved in the marriage process in Mekar Sari Village, Kubu Raya Regency. Madurese wedding traditions hold strong values, where marriage is not only considered a bond between two people but also a form of responsibility to family and society. In this research, the author used a qualitative case study approach, involving interviews with the bride and groom, their families, and traditional leaders, as well as direct observation of the wedding ceremony. The results show that in Madurese weddings, the values of family honor and social unity are highly valued. Wedding rituals are not just about ceremony, but also reflect the relationship between two extended families connected by long-standing traditions. Regarding gender roles, women are generally expected to maintain the family's dignity, while men play a greater role in economic matters and decision-making. However, over time, there has been a gradual shift in the younger generation's perspective on gender roles in marriage, with more couples beginning to discuss equality in their relationships. This research reveals that although Madurese wedding traditions and customs are still highly respected, changes are occurring as new values develop among young people. This demonstrates how culture and traditions can adapt to broader social dynamics while maintaining core values.